Serial Evaluation of Endometrial Blood Flow for Prediction of Pregnancy Outcomes in Patients Who Underwent Controlled Ovarian Hyperstimulation and In Vitro Fertilization and Embryo Transfer. (9th October 2017) - Koo, Hwa Seon; Park, Chan Woo; Cha, Sun Hwa; Yang, Kwang Moon
Abstract : Objectives: To investigate endometrial blood flow during the menstrual cycle in patients undergoing controlled ovarian hyperstimulation (COH), in vitro fertilization (IVF), and embryo transfer (ET) and prediction of pregnancy outcomes based on these characteristics. Methods: Endometrial blood flow was measured in 35 patients undergoing COH and IVF‐ET (nonpregnant [n = 15] and pregnant [n = 20]) by measuring the resistive index (RI) of the uterine radial artery using 2‐dimensional Doppler ultrasonography. Measurements were obtained in 4 different phases of the menstrual cycle day: early follicular, midfollicular, preovulatory, and midluteal. Results: The uterine radial artery RI during the early follicular phase was significantly lower in the pregnant group than in the nonpregnant group (mean ± SD, 0.61 ± 0.01 versus 0.66 ± 0.01; P = .029). There was no significant difference between groups during the midfollicular, preovulatory, and midluteal phases (mean ± SD, 0.60 ± 0.02 versus 0.60 ± 0.01; P = .84; 0.61 ± 0.09 versus 0.57 ± 0.01; P = .12; 0.54 ± 0.01 versus 0.57 ± 0.02; P = .32, respectively). There was a significant difference in endometrial blood flow between the pregnant and nonpregnant groups during each phase ( P = .016). The difference in the changes of the uterine radial artery RI from the preovulatory to midluteal phase between the pregnant and non pregnant groups was significant (−0.002 ± 0.03 versus 0.07 ± 0.02; P = .038). Conclusions: Increased endometrial blood flow during the midluteal phase, compared to the preovulatory phase, may correlate with successful COH and IVF‐ET. Additionally, sufficient blood flow at initiation of COH may affect COH and IVF‐ET results.